PENGARUH KEBIJAKAN HUTANG, PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Pertambangan dan Pertanian yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Agausto Saputra; Raja Adri Satriawan Surya; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
One of the goals of the company is founded is to maximize the firm value which is reflected in the share price of the company. Some varibel that affect the firm value has been investigated by researchers before.This research aims to empirically examines and analyze the influence of the company policy which consists of debt policy, profitability, company size, and managerial ownership to firm value. The research population is all mining and agriculture companies listed in Indonesia Stock Exchange period 2013-2016. The sample of research is selected based on purposive sampling method based on some criterias. Based on the criterias obtained 17 companies selected to be sampled. While the number of observations of 68 observations. The analysis technique used multiple linear regression analysis using SPSS ver. 20 computer program. The results of this study indicate that debt policy influence to firm value with significance value 0,034 (<0,05), profitability has no effect to firm value with a significance value of 0.358 (> 0.05), company size influence to firm value with significance value 0,042 (<0,05), and managerial ownership influence to firm value with significance value 0,000 (<0,05).Keywords : Debt Policy, Profitability, Company Size, Managerial Ownership, Firm Value